Unraveling the impact of pore length on the conversion reaction of Fe3O4/carbon anodes in lithium-ion batteries - Ryu, Jin; Park, Jongyoon; Lim, Won Gwang; Hwang, Jongkook (Applied Surface Science, 2024)
Despite numerous studies investigating Fe3O4/porous carbon anode materials for high-performance lithium-ion batteries (LIBs), the inherent limitations of the Fe3O4 conversion reaction, such as low reversibility and sluggish kinetics, continue to pose significant challenges. While modifying the porous structure of Fe3O4 anodes has demonstrated considerable promise in overcoming these limitations, the precise relationship between the porous structure and Fe3O4 conversion behavior still remains unclear. Here, we explore the impact of the pore length of the anode active material on the electrochemical performance of LIBs. Using two different composites of Fe3O4 and porous carbon with varying pore lengths as model materials, we conduct various in-depth electrochemical and ex-situ analyses. Our findings confirm that a shorter pore length facilitates higher Li+ ion diffusivity compared to longer pore length. Consequently, the conversion reaction of Fe3O4 to Fe and Li2O during lithiation process can be expedited, leading to a decrease in the resistance at the solid electrolyte interphase. As a result, we demonstrate that shortening the pore length of the porous anode composite materials can enhance the initial Coulombic efficiency (CE), reversible capacity, and rate capability of LIBs.
Keywords: Anode material; Conversion reactions; Ion batteries; Li +; Li+ ion diffusivity; Lithium ions; Pore length; Porous anode; Porous carbons; Porous structures; Conversion reaction; Li+ ion diffusivity; Lithium-ion battery; Pore length; Porous anode materials